An all-in-one homogeneous DNA walking nanomachine and its application for intracellular analysis of miRNA - Hu, Muren (Theranostics, 2019)
DNA walker is a powerful type of DNA nanomachine that can produce amplified signals during the "burnt-bridge"-like walking process. Despite their successful application in extracellular bioanalysis, the heterogeneity of the existing DNA walkers makes it difficult to guarantee the consistency of the results during the analysis of different cells. Methods: Here, an all-in-one homogeneous DNA walking nanomachine is reported that can be delivered into living cells for intracellular bioanalysis of miRNA without auxiliary materials. Results: This DNA walking nanomachine is constructed of gold nanoparticles on which two types of interrelated DNA tracks are assembled. The target miRNA, cancer-related miR-21, can be captured by one of the tracks (track 1) and then walk to the other track (track 2), releasing the hybrid of track 1 and track 2 from the nanoparticle to produce a signal. The walking process can proceed in a cyclic 1-2-1-2 manner and thereby produce amplified signals. Thus, sensitive imaging of the miRNA in situ can be achieved. Conclusion: Benefiting from the homogeneity of the detection system, the method can be applied for intracellular analysis without interference induced by the fluctuations of stimuli or accessorial contents.